Voiceless shout: Parents\\\' experience of caring for child with cerebral palsy - Nasrin Alaee; Farahnaz Mohammadi-Shahboulaghi; Hamid Reza Khankeh; Sima Mohammad Khan Kermanshahi (Tehran University of Medical Sciences, 2013)
Background & Aim: Children with cerebral palsy need permanent care and attention in various stages of growth and development. The parents experience problems in taking care of these children and making them independent. This study was conducted to explore these experiences.   Methods & Materials : This qualitative study was conducted in 2011-2012 using content analysis. Purposeful sampling was used to recruit 19 parents of children with cerebral palsy referred to rehabilitation centers in Tehran. The data were gathered using in-depth and semi-structured interviews and were analyzed inductively.   Results: Data analysis results revealed three original categories including "life with hardness" ، "being in ambiguity" ، and "need to be supported" ، and several subcategories including "physical strain" ، "psycho-emotional strain" ، financial burden" ، "restriction in social activities"; "facing with anonymous" ، "lack of having an advisor" ، "need to get help from professionals and specialists" ، "need to have emotional- spiritual support" ، and "need to have help in caring the child".   Conclusion : Parents in permanent care of children with cerebral palsy face with new and various situations consistently and experience difficulty and bewilderment because of insufficient family and social support. Further studies are needed to explore the support process of caregiver parents of these children.